INCOTERMS as a form of standardisation in international sales law : an analysis of the interplay between mercantile custom and substantive sales law with specific reference to the passing of risk - Coetzee, Juana (Stellenbosch : University of Stellenbosch, 2010)
Thesis (LLD (Mercantile Law))--University of Stellenbosch, 2010.